Impact of Office Digitalization on the Productivity Level of the Administrative Personnel in Pantawid Pamilyang Pilipino Program, Quezon City: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Pantawid Pamilyang Pilipino Program (4Ps), implemented by the Department of SocialWelfare and Development (DSWD), is a national government human development programthat invests in the health and education of poor households, particularly children aged 0-18years old. President Rodrigo Roa Duterte signed Republic Act No.11310, or An ActInstitutionalizing the Pantawid Pamilyang Pilipino Program (4Ps), on April 17, 2019, makingPantawid Pamilya the government's national poverty reduction policy. The use of computerand communication technology that are integrated to support administrative activities in anoffice setting is commonly thought of as digitalization. Automated office systems are well-organized methods of managing in the workplace.The implementation of office digitalization should be monitored and evaluated to identify anyissues and to make necessary improvements. By following these recommendations, andorganizations can effectively implement office digitalization to improve the productivity level ofadministrative personnel in the office environment, leading to increased efficiency, cost-effectiveness, and overall workplace performance.The study concludes that office digitalization has the potential to significantly enhance theproductivity level of administrative personnel. However, it is important for organizations toprovide adequate training and support for administrative personnel to ensure that they areable to effectively utilize digital tools to increase productivity. Overall, the findings of this studycontribute to our understanding of the impact of office digitalization on the productivity level ofadministrative personnel and have important implications for organizations seeking to improveefficiency and productivity in their administrative functions.
Keywords: Organisational Management